Caracterización del Perfil Hematológico y Bioquímico del Lagomorfo Silvestre Ecuatoriano en la Provincia de Cotopaxi. - Reinoso Herrera, Karina de los Angeles (2018)
The following research is based on Characterization of the haematological and biochemical wild lagomorph. For the lack of information in Ecuador it was developed in 30 animals in the high lands of Ticatilin, Pansachi y Baños in the province of Cotopaxi. The height is about 3600 to 4200 above sea level, the animals were captured by snares, blood samples were obtained of the vein, where it was collected 1 to 2 ml. it was placed tubes with minicollet with and without anticoagulant where all the standards were taken for sending the samples to the San Francisco laboratory. The variables evaluated in the blood count were; (Hematocrit, Hemoglobin, Erythrocytes, Average Corpuscular Volume and Platelets), about white series; (Leukocytes, Heterophiles, Lymphocytes, Monocytes, Eosinophils and Basophils) and relating to the to serum biochemistry (Glucose, Urea, Bun, Creatinine, Total Proteins, Aspartate Aminotransferase, Alanine Ami notransferase, Calcium, Phosphorus and Potassium). The analysis results was carried out by the method of multiple comparison and descriptive statistics, the results showed average values for rabbits in hematocrit, 41,25 - 45,34 %, hemoglobin 11,74 - 15,84 (g/dl), erythrocytes (〖10〗^6/µL) 4,63 - 8,72, leukogram, leukocytes(10^3 μl) 3 - 7,09, heterophiles % 28,99 - 33,08, and the biochemical profile, glucose (mmol/L) 4,77 - 8,86, urea (mmol/L) 5,98 - 10,07,calcium (mmol / L) 1.51-5.6. It was determined between males and females there are no differences, relating to the analysis there is a meaningful difference between leucogram and biochemical variables. The environment and nourishment stablish the animals ‘health, showing with better features to lagomorph form Pansachi high land.